Label-free ferrohydrodynamic cell separation of circulating tumor cells. Issue 18 (15th August 2017) - Zhao, Wujun; Cheng, Rui; Jenkins, Brittany D.; Zhu, Taotao; Okonkwo, Nneoma E.; Jones, Courtney E.; Davis, Melissa B.; Kavuri, Sravan K.; Hao, Zhonglin; Schroeder, Carsten; Mao, Leidong
Abstract : A size-based ferrohydrodynamic cell separation (FCS) device capable of enriching intact circulating tumor cells with high throughput and high recovery rate. Abstract : Circulating tumor cells (CTCs) have significant implications in both basic cancer research and clinical applications. To address the limited availability of viable CTCs for fundamental and clinical investigations, effective separation of extremely rare CTCs from blood is critical. Ferrohydrodynamic cell separation (FCS), a label-free method that conducted cell sorting based on cell size difference in biocompatible ferrofluids, has thus far not been able to enrich low-concentration CTCs from cancer patients' blood because of technical challenges associated with processing clinical samples. In this study, we demonstrated the development of a laminar-flow microfluidic FCS device that was capable of enriching rare CTCs from patients' blood in a biocompatible manner with a high throughput (6 mL h −1 ) and a high rate of recovery (92.9%). Systematic optimization of the FCS devices through a validated analytical model was performed to determine optimal magnetic field and its gradient, ferrofluid properties, and cell throughput that could process clinically relevant amount of blood. We first validated the capability of the FCS devices by successfully separating low-concentration (∼100 cells per mL) cancer cells using six cultured cell lines from undiluted white blood cells (WBCs), with an average 92.9% cancer cell recovery rate and an average 11.7% purity of separated cancer cells, at a throughput of 6 mL per hour. Specifically, at ∼100 cancer cells per mL spike ratio, the recovery rates of cancer cells were 92.3 ± 3.6% (H1299 lung cancer), 88.3 ± 5.5% (A549 lung cancer), 93.7 ± 5.5% (H3122 lung cancer), 95.3 ± 6.0% (PC-3 prostate cancer), 94.7 ± 4.0% (MCF-7 breast cancer), and 93.0 ± 5.3% (HCC1806 breast cancer), and the corresponding purities of separated cancer cells were 11.1 ± 1.2% (H1299 lung cancer), 10.1 ± 1.7% (A549 lung cancer), 12.1 ± 2.1% (H3122 lung cancer), 12.8 ± 1.6% (PC-3 prostate cancer), 11.9 ± 1.8% (MCF-7 breast cancer), and 12.2 ± 1.6% (HCC1806 breast cancer). Biocompatibility study on H1299 cell line and HCC1806 cell line showed that separated cancer cells had excellent short-term viability, normal proliferation and unaffected key biomarker expressions. We then demonstrated the enrichment of CTCs in blood samples obtained from two patients with newly diagnosed advanced non-small cell lung cancer (NSCLC). While still at its early stage of development, FCS could become a complementary tool for CTC separation for its high recovery rate and excellent biocompatibility, as well as its potential for further optimization and integration with other separation methods.